2015
DOI: 10.1186/s12882-015-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

A microrna screen to identify regulators of peritoneal fibrosis in a rat model of peritoneal dialysis

Abstract: BackgroundPeritoneal fibrosis is a common complication in patients treated with long-term peritoneal dialysis. The aim of this study was to identify the microRNAs (miRNAs) involved in regulation of peritoneal fibrosis in a rat model of peritoneal dialysis.MethodsTwenty-four Sprague–Dawley (SD) rats were randomly allocated into three groups: (i) Control group (Cg, n = 8); (ii) Saline group (Sg, n = 8): daily intraperitoneal injection with 0.9% normal saline; (iii) Hypertonic dialysate group (HDg, n = 8): daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Previous studies have presented evidence highlighting the key role played by RNAs in the formation of PD‐induced PF (19, 20). Liu et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have presented evidence highlighting the key role played by RNAs in the formation of PD‐induced PF (19, 20). Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have presented evidence highlighting the key role played by RNAs in the formation of PD-induced PF (19,20). Liu et al (13), after sequencing the normal control peritoneum and PDF-induced fibrotic peritoneum, found 232 differentially expressed lncRNAs, among which AK089579 may play a key role in the formation of PF.…”
Section: Microarray-based Gene Expression Profiling Of Pfmentioning
confidence: 99%
“…Among them, miRNA microarray technology is a specific and efficient method to generate miRNA expression profiles. This approach has been applied to study the functional linkages between miRNAs and physiological/pathological processes . In this study, a microarray that included 5214 mature human miRNAs on the array chip was employed to analyse miRNA expression systematically in the LPS‐treated PDLCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, a limited number of studies investigated the role of miR-152 in the urinary system. In a recent study, Lin et al (31) demonstrated that miR-152 expression was significantly downregulated in a rat model of peritoneal fibrosis, suggesting its involvement in the pathogenesis of peritoneal fibrosis. Therefore, in the present study, it was hypothesized that miR-152 may serve similar roles in EMT of tubular epithelial cells and the progression of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%